From where they stood - Cognet, Christophe 1966-; Bozon, Céline 1975- (Kino Lorber, 2022)
"It is not widely known that a handful of prisoners in the Nazi death camps managed somehow to take clandestine photographs of the hell that was being hidden from the world. Director Christophe Cognet retraces the footsteps of these courageous men and women in a quest to unearth the circumstances and the stories behind their photographs.]" [kinolorber.com]
Original: Frankreich, Deutschland 2021
Bildformat 1.66:1 (16:9)
Keywords: Geschichte 1933-1945; Gefangener; Konzentrationslager; Fotografie; Deutschland; Film; DVD-Video